Measurement of Grain Boundary Properties in Cu(ln, Ga)Se2 Thin Films. (8th May 2018) - Rozeveld, S.; Reinhardt, C.; Bykov, E.; Wall, A.
Abstract: Abstract: Semiconductors CulnSe2 (CIS) and alloys of Cu(ln, Ga)Se2 (CIGS) are often used as the light absorbing layer in thin film photovoltaic devices. These polycrystalline materials reach good conversion efficiencies despite the presence of grain boundaries, which can degrade device performance. Grain properties such as size distribution and orientation can be characterized using electron backscatter diffraction (EBSD). The EBSD method has been used extensively to determine texture and recrystallization in metal forming processes but to a lesser extent for characterization of CIGS thin film properties. This article describes measurements of grain properties for CIGS thin films grown under different reaction conditions.